KONSEP DIRI POSITIF PENDIDIK DALAM MENGIINTEGRASIKAN NILAI-NILAI MORAL DALAM PEMBELAJARAN PSIKOLOGI - Enjoni Enjoni; Wirnita Wirnita (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2021)
AbstractEducators play a very important role for the progress of the institution and the formation of the character of students. However, it is no secret that many educators, namely lecturers neglect the main task of teaching, exemplary lecturers and the application of moral values during Educational Psychology lectures shape the character of students' obedience and honesty. The purpose of this study was to determine the impact of lecturer's example and the application of moral values in Educational Psychology lectures on the formation of students' obedience and honesty characters.This study provides and analyzes related to the positive self-concept of an educator in applying moral values in learning psychology. Based on the descriptive analysis of this paper, it is hoped that this paper can provide input / insight to education personnel, so that they understand positive self-conceptThe results showed that the positive concept of an educator in the form of always giving an example of arriving on time in teaching Educational Psychology courses can improve the character of obedience and the formation of student character, namely arriving on time or not late in attending lectures and having good character. Likewise, lecturers who insert moral values while teaching Educational Psychology courses can have an impact on the formation of students' honesty character, namely honest behavior or not cheating on exams.Keywords: Lecturer, Positive self-concept, Student character